2020
DOI: 10.33567/etm.2263
|View full text |Cite
|
Sign up to set email alerts
|

Baromfi marketing – preferencia és vásárlás

Abstract: The consumption of poultry is an important source of nutrition, so it is a basic need for everyday food conception. To supply the population is not only a sensitive social question but also a question of national health. The aim of this study is to reveal the connection between the preference of poultry and the basic socio-demographic factors and highlight the circumstances of purchasing this type of meat. In order to understand the preference of poultry, a large sample of quantitative (n=1 023 respondents) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Poultry meat has increasingly evolved from a commercial product to a premium food product and is therefore no longer considered a product of the average consumer (Huszka et al, 2018). The demand for poultry products with added value and quality is expected to continue to grow among consumers of premium products (Aliczki et al, 2013;Huszka, 2017). Regarding meat consumption, Fehér and Szakály, 2017 found that Hungarians are most likely to eat poultry and pork.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Poultry meat has increasingly evolved from a commercial product to a premium food product and is therefore no longer considered a product of the average consumer (Huszka et al, 2018). The demand for poultry products with added value and quality is expected to continue to grow among consumers of premium products (Aliczki et al, 2013;Huszka, 2017). Regarding meat consumption, Fehér and Szakály, 2017 found that Hungarians are most likely to eat poultry and pork.…”
Section: )mentioning
confidence: 99%
“…In addition, consumers attach more and more importance to the origin of meat, and the way it is kept in accordance with animal welfare standards, they prefer quality consumption over quantity, and they are moving from consuming fresh meat to processed meat products (EC, 2018). The importance of the poultry sector in modern times is unquestionable since poultry products have become a basic food product (Huszka, 2017;Vincze and Lendvai, 2012) not only in Europe but in many countries of the world. The reason for this is that many components of these meats have a positive effect on our body from a nutritional and physiological point of view (Huszka, 2017), and compare with other types of meat, poultry is considered a cheaper type of meat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation